Field Evaluation of Black Soldier Fly (BSF) Frass as an Organic Fertilizer for Tomato - Cortez, Jeffrey; Martin, Artemio Jr (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to evaluate the effectiveness of Black Soldier Fly (BSF) frass as an alternative organic fertilizer for tomato production, focusing on its effects on plant growth, yield, fruit quality, and economic performance under field conditions. Grounded in the principles of sustainable agriculture, organic nutrient management, and circular bioeconomy, the research employed a Randomized Complete Block Design (RCBD) with treatments consisting of BSF frass applied alone and in combination with recommended inorganic fertilizers (120-60-60 kg NPK ha⁻¹). The experiment was conducted in a field setting using tomato plants (D-max F1), with data collected on growth parameters, yield components, fruit quality attributes, and economic indicators. Results showed that the combined application of BSF frass and inorganic fertilizers significantly improved plant height, branching, biomass, and yield compared to sole applications and the control. The highest yield (35.88 t ha⁻¹) and return on investment (804.03%) were obtained from the treatment combining inorganic fertilizer with 4.5 t ha⁻¹ BSF frass, indicating enhanced nutrient efficiency and profitability. However, higher rates of BSF frass reduced fruit quality parameters such as total soluble solids and vitamin C content, highlighting a trade-off between yield and quality. The study concludes that BSF frass is most effective when used as a complementary input rather than a sole fertilizer source, with recommended rates of 3.0–4.5 t ha⁻¹ combined with inorganic fertilizers to optimize productivity and economic returns. The findings support Sustainable Development Goals including Zero Hunger (SDG 2), Responsible Consumption and Production (SDG 12), Climate Action (SDG 13), and Life on Land (SDG 15), as the study promotes sustainable nutrient management, waste valorization, and improved soil health. The sustainability impact lies in enhancing environmentally sustainable agricultural practices, improving soil fertility, reducing reliance on synthetic fertilizers, and supporting economically viable and resource-efficient farming systems.
Keywords: Black Soldier Fly Frass; Circular Agriculture; Economic Performance; Fruit Quality; Integrated Nutrient Management; Sustainable Agriculture; Tomato Yield